Is Pulmonary Function Affected by Bilateral Dual Transversus Abdominis Plane Block? A Randomized, Placebo-Controlled, Double-Blind, Crossover Pilot Study in Healthy Male Volunteers. Issue 6 (1st October 2011) - Petersen, Maria; Elers, Jimmi; Børglum, Jens; Belhage, Bo; Mortensen, Jann; Maschmann, Christian
Abstract : Background and Objectives: Transversus abdominis plane (TAP) blocks have been shown to reduce postoperative pain after various abdominal surgical procedures in several studies. The motor nerves of the abdominal wall are located in the same plane as the sensory nerves affected by the TAP block. The aim of this study was to examine whether the application of an ultrasound-guided TAP block would affect the muscles of the anterior abdominal wall with respect to their function as accessory respiratory muscles and hence pulmonary function. Methods: Twelve healthy male volunteers were included in a randomized, double-blind, crossover study. Primary outcome measure was change in forced expiratory volume in 1 sec (FEV1 ) after the bilateral dual injection of either 4 × 15 mL of 0.25% bupivacaine or saline. Secondary outcome measures included forced vital capacity, maximum expiratory pressure, and a number of frontal abdominal quadrants anesthetized. Results: Change in FEV1 following the administration of bupivacaine showed a mean increase of 15 (SEM, 45.5) mL compared with the saline block, which showed a mean increase in FEV1 of 34 (SEM, 57.4) mL ( P = 0.62). Similar results were obtained for forced vital capacity and maximum expiratory pressure. Abdominal quadrants were inconsistently anesthetized following administration of bupivacaine blocks. Conclusions: The administration of ultrasound-guided bilateral dual TAP blocks does not result in clinically relevant or statistically significant changes in the pulmonary function in healthy male subjects.